The Success of Employee Self-Service Portals - Verlaan, Patrick (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Employee self-service portals support the business processes of organizations, because these portals can cut costs and improve employee satisfaction. However, it was not clear which self-service features should be included in employee portals. The goal of this research was to determine which key features should be included in employee self-service portals. Different self-service feature categories have been identified for this research: HR information, IT services, procurement, time or expense reporting, and training. The updated IS Success model by DeLone & McLean (2003) has been used to identify the relevant constructs to test the success of the different self-service feature categories. The dimensions (Intention to) Use, Use Satisfaction and Benefits (e.g. cost reduction) have been used for this research. Three cases studies have been conducted to test the conceptual model. A questionnaire was sent to end-users of self-service portals to test the effects of the five self-service features categories on Intention to Use and User Satisfaction. Interviews were held with decision-makers to test the relationship between Use and Cost Reduction. The results showed positive effects of the self-service feature categories on Intention to Use and User Satisfaction. Therefore, it is suggested that organizations implement self-service portals. When organizations would like that their employees are willing to use self-service portals then features for HR information, IT services and, time or expense reporting should be available. Furthermore, when organizations would like to emphasize the user satisfaction then self-service portals for IT services, and time or expense reporting should be implemented. The positive effects of User Satisfaction on Intention to Use and Use on User Satisfaction have also been proven. The case studies showed that cost reduction is not one of the main reasons for the organizations to implement self-service portals. The interviewees mentioned improvement of business processes as main reason to implement self-service portals. The relationship between Use and Cost reduction has not been supported in this research.